Peptidoglycan Recognition Protein S2 From Silkworm Integument: Characterization, Microbe-Induced Expression, and Involvement in the Immune-Deficiency Pathway. Issue 1 (22nd March 2015) - Yang, Jie; Wang, Xiaonan; Tang, Shunming; Shen, Zhongyuan; Wu, Jinmei
Abstract : Peptidoglycan recognition protein (PGRP) binds specifically to peptidoglycan and plays an important role as a pattern recognition receptor in the innate immunity of insects. The cDNA of a short-type PGRP, an open reading frame of 588 bp encoding a polypeptide of 196 amino acids, was cloned from Bombyx mori . A phylogenetic tree was constructed, and the results showed that BmPGRP-S2 was most similar to Drosophila melanogaster PGRP ( DmPGRP-SA ). The induced expression profile of BmPGRP-S2 in healthy Escherichia coli - and Bacillus subtilis- challenged B. mori was measured using semiquantitative reverse transcriptase polymerase chain reaction analysis. The expression of BmPGRP-S2 was upregulated at 24 h by E. coli and Ba. subtilis challenge. In addition, in the integument of B. mori, RNAi knockdown of BmPGRP-S2 caused an obvious reduction in the transcription expression of the transcription factor Relish and in antibacterial effector genes Attacin, Gloverin, and Moricin . The results indicated that BmPGRP-S2 participates in the signal transduction pathway of B. mori .